Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.nanolett.5b00267
|View full text |Cite
|
Sign up to set email alerts
|

Quenched Phonon Drag in Silicon Nanowires Reveals Significant Effect in the Bulk at Room Temperature

Abstract: Existing theory and data cannot quantify the contribution of phonon drag to the Seebeck coefficient (S) in semiconductors at room temperature. We show that this is possible through comparative measurements between nanowires and the bulk. Phonon boundary scattering completely quenches phonon drag in silicon nanowires enabling quantification of its contribution to S in bulk silicon in the range 25-500 K. The contribution is surprisingly large (∼34%) at 300 K even at doping of ∼3 × 10(19) cm(-3). Our results cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…Boukai et al [ 7 ] studied highly doped individual Si nanowires of diameter 10 and 20 nm and reported an anomalous phonon drag enhancement at room temperature. A recent study on an array of Si nanowires with diameter ~100 nm and doping concentration ~10 19 cm −3 (surface roughness 0.4 nm) [ 30 ] contradicts the above and concludes that at 300 K, boundary scattering of phonons in the specific Si nanowires (which were highly doped) completely quenches drag and reduces S . If we now consider Si nanocrystals, recent studies [ 32 ] demonstrated experimentally that in quite small nanocrystals, of diameter 2.4 nm, the Seebeck coefficient was by one order of magnitude lower than in nanocrystals with sizes of 5.6 and 8.3 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Boukai et al [ 7 ] studied highly doped individual Si nanowires of diameter 10 and 20 nm and reported an anomalous phonon drag enhancement at room temperature. A recent study on an array of Si nanowires with diameter ~100 nm and doping concentration ~10 19 cm −3 (surface roughness 0.4 nm) [ 30 ] contradicts the above and concludes that at 300 K, boundary scattering of phonons in the specific Si nanowires (which were highly doped) completely quenches drag and reduces S . If we now consider Si nanocrystals, recent studies [ 32 ] demonstrated experimentally that in quite small nanocrystals, of diameter 2.4 nm, the Seebeck coefficient was by one order of magnitude lower than in nanocrystals with sizes of 5.6 and 8.3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In bulk semiconductors at room temperature, the phonon drag effect is in general considered to be important in the case of the undoped or lightly doped material and smaller in the heavily doped material. Figure 8 shows some representative data from the literature [ 30 , 31 ] relating S , S d and S ph with doping concentration in the case of bulk Si. A large dependence of S on doping is observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In addition to this, the role of the coupled electron-phonon dynamics on the thermoelectric properties of silicon has very recently attracted renewed interest. [11][12][13] Indeed, in this material there is a substantial enhancement, even at room temperature and in heavily doped samples, of the Seebeck coefficient induced by the drag exerted on charge carriers from phonons diffusing along a temperature gradient (phonon drag). In the past this topic has not received much attention beyond the initial experimental 14 and theoretical 15 works, but with current interest in thermoelectric energy conversion this effect might represent an interesting route to enhance thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…The notion that phonon drag is suppressed in highly doped bulk samples stems partly from a conclusion reached by Weber and Gmelin 12 , who revisited the classic measurements of Geballe and Hull 24 with modifications of their own. Weber and Gmelin considered the low temperature (< 40 K) part 24 , Weber et al 12 , and Sadhu et al 11 ) for bulk silicon is shown for comparison. The dashed curves are theoretical calculations of the diffusion part of S assuming carrier concentrations listed in Table I. of their data for degenerately doped Si and claimed S ∼ T in that range.…”
Section: Discussionmentioning
confidence: 99%